From perception to action a social-cognitive analysis of students’ responses to general studies curriculum implementation and their impact on academic performance and curriculum design - Lei Shi; Ian R. Lana (Environment and Social Psychology, 2025)
This environmental and social-cognitive research evaluated the General Studies Teaching Program implementation and its effectiveness on student performance within educational ecosystems, aiming to improve curriculum development through understanding person-environment-society interactions that influence academic outcomes. Grounded in Taba’s model and informed by environmental psychology and social-cognitive theory, the study examined curriculum aspects as environmental affordances and social learning opportunities across seven dimensions: environmental needs diagnosis, objective formulation, content selection, content organization, learning activity selection and organization, and evaluation systems. The study comprised 380 students from four universities in Heilongjiang, China, representing diverse environmental contexts within the regional educational ecosystem. Environmental and social-psychological analysis revealed that while the curriculum demonstrated general effectiveness in providing environmental affordances (M=4.06 for needs diagnosis), significant deficiencies emerged in environmental organization (M=2.71) and experiential learning opportunities (M=3.25) that limit students’ environmental competence and social-cognitive development. Statistical analysis indicated significant demographic differences across academic levels, with transfer students experiencing particular environmental transition stress and social adaptation challenges. Environmental learning activities, social collaboration organization, and feedback systems demonstrated statistically significant influence on academic performance, suggesting these factors serve as critical mediators in the perception-to-action pathway. Average academic performance was 75.3% with substantial variability (60%-89%), indicating disparities in environmental competence and social support access that create inequitable learning ecosystems. To address these environmental and social-cognitive deficiencies, a comprehensive curriculum enhancement framework is recommended that integrates environmental psychology principles with social-cognitive theory, focusing on environmental design improvements, social integration strategies, and differentiated support systems that promote both individual environmental flourishing and collective social transformation within inclusive educational communities.